The Role of Pulmonary Metastasectomy in Breast Cancer with Limited Progression Following CDK4/6 Inhibitor Therapy: A Case Report - Yu-Ting Su; Shang-Hung Chen (Journal of Cancer Research and Practice)
Metastatic breast cancer is primarily managed with systemic therapy; however, the role of pulmonary metastasectomy (PM) in patients with pulmonary oligometastases remains uncertain. We present the case of a 56-year-old postmenopausal woman who developed lung and bone metastases 4 years after resection of her primary tumor. Due to the progression of pulmonary metastasis following combined therapy with ribociclib and fulvestrant for advanced disease, she underwent PM, which histologically confirmed breast cancer metastasis. Following the procedure, she continued the same combined therapy and achieved stable disease. This case highlights that PM can aid in the accurate differential diagnosis of lung nodules in breast cancer patients. For selected individuals, particularly those with limited progression following CDK4/6 inhibitor therapy, PM may be considered an additional treatment option.